2015
DOI: 10.1007/s11009-015-9462-7
|View full text |Cite
|
Sign up to set email alerts
|

Option Pricing Under Jump-Diffusion Processes with Regime Switching

Abstract: We study an incomplete market model, based on jump-diffusion processes with parameters that are switched at random times. The set of equivalent martingale measures is determined. An analogue of the fundamental equation for the option price is derived. In the case of the two-state hidden Markov process we obtain explicit formulae for the option prices. Furthermore, we numerically compare the results corresponding to different equivalent martingale measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Also for s ∈ [0, t ∧ ς ∆,n ], we obtain from the Lyapunov function in (15) and the mean value theorem that…”
Section: Strong Convergencementioning
confidence: 99%
See 2 more Smart Citations
“…Also for s ∈ [0, t ∧ ς ∆,n ], we obtain from the Lyapunov function in (15) and the mean value theorem that…”
Section: Strong Convergencementioning
confidence: 99%
“…The shortcoming of the continuous-time model of Black-Scholes [1] in describing convex phenomena of implied volatility exhibited by most historical financial data led to the underlying assumption of constant volatility to be questioned. Several empirical studies have rather shown that stochastic volatility models with inherent features of past dependency are suitable models for describing convex phenomena of implied volatility against market anomalies (see, e.g., [2,8,9,15]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation